Bacterially Produced, Nacre‐Inspired Composite Materials. Issue 22 (5th April 2019) - Spiesz, Ewa M.; Schmieden, Dominik T.; Grande, Antonio M.; Liang, Kuang; Schwiedrzik, Jakob; Natalio, Filipe; Michler, Johann; Garcia, Santiago J.; Aubin‐Tam, Marie‐Eve; Meyer, Anne S.
Abstract: The impressive mechanical properties of natural composites, such as nacre, arise from their multiscale hierarchical structures, which span from nano‐ to macroscale and lead to effective energy dissipation. While some synthetic bioinspired materials have achieved the toughness of natural nacre, current production methods are complex and typically involve toxic chemicals, extreme temperatures, and/or high pressures. Here, the exclusive use of bacteria to produce nacre‐inspired layered calcium carbonate‐polyglutamate composite materials that reach and exceed the toughness of natural nacre, while additionally exhibiting high extensibility and maintaining high stiffness, is introduced. The extensive diversity of bacterial metabolic abilities and the possibility of genetic engineering allows for the creation of a library of bacterially produced, cost‐effective, and eco‐friendly composite materials. Abstract : The exclusive use of bacteria to produce nacre‐inspired layered calcium carbonate‐polyglutamate composite materials that match and exceed the toughness of natural nacre, while additionally exhibiting high extensibility and maintaining high stiffness, is introduced. The extensive diversity of bacterial metabolic abilities and the possibility of genetic engineering allows for creating a library of bacterially produced, cost‐effective, and eco‐friendly composite materials.